2007
DOI: 10.1097/01.bot.0000211163.51605.ae
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk With Ketorolac After Lumbar Microdiscectomy

Abstract: There is a need to improve postoperative analgesia to support the trend to shorter hospitalization after minimally invasive spine surgeries. Ketorolac Tromethamine has proven efficacy in decreasing postoperative pain but there is concern with postoperative epidural bleeding after spine procedures. We prospectively assessed the incidence of bleeding complications after microdiscectomy in patients treated with a single 30 mg intraoperative dose of Ketorolac subsequent to wound closure. Group 1 consisted of 44 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The results suggest no relationship between ketorolac use and radiographic or clinically significant bleeding events in the postoperative period. In combination with previous studies regarding the efficacy of ketorolac in decreasing narcotic usage, 1,2,5,11,14,15,20,23 as well as the rationale for minimizing the use of sedating medications following neurosurgery, this study supports ketorolac as an option in the perioperative setting among the pediatric neurosurgical population. The role of perioperative ketorolac in pediatric neurosurgery should be further explored through larger prospective studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results suggest no relationship between ketorolac use and radiographic or clinically significant bleeding events in the postoperative period. In combination with previous studies regarding the efficacy of ketorolac in decreasing narcotic usage, 1,2,5,11,14,15,20,23 as well as the rationale for minimizing the use of sedating medications following neurosurgery, this study supports ketorolac as an option in the perioperative setting among the pediatric neurosurgical population. The role of perioperative ketorolac in pediatric neurosurgery should be further explored through larger prospective studies.…”
Section: Discussionsupporting
confidence: 76%
“…Some clinical safety studies have demonstrated that administration of NSAIDs leads to an increase in postoperative bleeding events, 3,9,10,19,20 whereas other studies have demonstrated the NSAIDs can be safely administered postoperatively. 11,13,14,17,18,23,25,26,28 Since 2000, we have routinely used ketorolac as a component of the perioperative analgesic regimen during the first 72 hours following pediatric neurosurgical procedures. We sought to assess whether this strategy was associated with an increased risk for hemorrhagic or systemic complications.…”
mentioning
confidence: 99%
“…For example, in a study of patients undergoing lumbar discectomy, a single dose of intraoperative intravenous ketorolac provided effective pain control with no observed difference between groups with respect to bleeding-related complications. 13 Likewise, Vitale et al conducted a retrospective review of 208 children who underwent scoliosis surgery, and they determined that postoperative ketorolac administration was not associated with an increased requirement for blood transfusion or reoperation. 14 In contrast, RuDusky et al…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is a paucity of literature in the use of ketorolac with hand procedures in particular, it has been looked at in the spine literature where Chin et al 53 found no risk of bleeding complications compared with that of their control group in patients having microdiscectomy after a single intraoperative dose of ketorolac.…”
Section: Ketorolacmentioning
confidence: 99%